Socioeconomic factors affecting Siwalan Sugar Business income. Case study in Jadung Village, Dungkek District, Sumenep Regency - Ainorrofiqie; Annisa Zhafarina Qosasi (Technium Social Sciences Journal, 2023)
Siwalan is one of the community’s agricultural crops, where this plant is often found in rural areas, and this plant is one of the crops that are managed in the small-scale agricultural business sector, the management of this agricultural business sector is classified as traditional both in terms of management methods and tools, because this business sector is an agricultural business that has been passed down from generation to generation. Palm plants are very beneficial for rural communities, because from all parts of the palm plant can almost be used. The results that can be produced from this plant are sap and palm fiber. The purpose of this research is the first to determine the factors that affect palm sugar business income, the second to determine the most dominant factors that affect palm sugar business income. This type of research is a quantitative study using multiple linear regression analysis method. The object of this research is Jadung Village, Dungkek District, Sumenep Regency with a research sample of 70 respondents. The results showed that the variables age, education, length of business, number of dependents, number of trees, and cosmopolitan level had a significant effect on palm sugar business income. Based on the results of research on socio-economic factors that affect palm sugar business income, it shows that. Socio-economic factors that affect palm sugar business income are age, education, length of business, family dependents, number of trees and cosmopolitan level, both jointly and partially. The most dominant factor that affects palm sugar business income in Jadung Village, Dungkek District, Sumenep Regency is the Number of Trees Factor, this can be seen from the amount of the beta coefficient variable the number of trees which is 0.396 greater than the others.